2008
DOI: 10.1080/11263500802410918
|View full text |Cite
|
Sign up to set email alerts
|

In vitro olive (Olea europaeaL.) cvs Frantoio and Moraiolo microshoot tolerance to NaCl

Abstract: In vitro culture of rooted and unrooted olive microshoots, established from seed lines of free-pollinated ''Frantoio'' and ''Moraiolo'' cultivars, were evaluated for NaCl tolerance. The aim was to use growth and physiological parameters in order to identify salt-adapted genotypes. Leaf tissue elemental distribution of Na, Cl and K was also investigated in unrooted plantlets by cryo-scanning electron microscopy and energy-dispersive X-ray microanalysis. Both in unrooted and rooted plantlets, increased concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In addition, the ultrastructural changes at the nuclear and cytoplasm level (Bennici and Corrado 2009) in different parts of the axillary shoots due to toxic concentrations of salt might have contributed to reduced growth. As in our study, the sodium concentration was more than 10 mmol g -1 DW; the response of growth reduction might be specifically attributed to the toxic concentration of sodium ions rather than the nutritional disturbance, which is in agreement with Vicente et al (2004) and Bracci et al (2008). The accumulation of sodium and concomitant decrease in potassium levels appear to be one of the general characteristics of halophytes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, the ultrastructural changes at the nuclear and cytoplasm level (Bennici and Corrado 2009) in different parts of the axillary shoots due to toxic concentrations of salt might have contributed to reduced growth. As in our study, the sodium concentration was more than 10 mmol g -1 DW; the response of growth reduction might be specifically attributed to the toxic concentration of sodium ions rather than the nutritional disturbance, which is in agreement with Vicente et al (2004) and Bracci et al (2008). The accumulation of sodium and concomitant decrease in potassium levels appear to be one of the general characteristics of halophytes.…”
Section: Discussionsupporting
confidence: 83%
“…The possibility and the advantages of using in vitro shoot cultures to evaluate salt tolerance have been reported in many plants such as tomato (Cano et al 1998), rice (Basu et al 2002), mulberry (Vijayan et al 2003), Plantago crassifolia (Vicente et al 2004) and Olea europaea (Bracci et al 2008). Most of these investigators indicated shoot cultures as the best choice for physiological studies because many of the plant responses to salt stress are due to an integrated functioning of shoots and roots in toxic ions exclusion or inclusion that cannot be evidenced in callus and cell cultures (Vijayan et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Reductions in growth and yield due to salinity have been widely reported Chartzolulakis et al, 2002;Chartzoulakis 2005;Bracci et al, 2008). Longterm studies with trees under field conditions by Aragües et al (2005) with 'Arbequina' trees show that above 4 dS m -1 EC, reductions in yield ranging from 16 to 23% per 1 dS m -1 occurred.…”
Section: Salinitymentioning
confidence: 90%
“…Furthermore, although the root system is the first plant organ to be affected by salt stress, and root traits are thought to be among the most useful tools in evaluating and screening of salt tolerance (e.g. for olive see Bracci et al 2008), most studies have focussed on above-ground organs (e.g. Demiral 2005;Junghans et al 2006).…”
Section: Introductionmentioning
confidence: 99%